Opportunities of educational e-resources development based on Moodle for students learning foreign languages (Pedagogy of Higher and Secondary Education, 2015)
Tomilina A. A. Opportunities of educational e-resources development based on Moodle for students learning foreign languages.The opportunities of e-learning Moodle which are corresponded to the Ukrainian educational standards are distinguished in the article. The author describes her own practicalexperience of educational e-courses development for language students on the web-portal of Kryvyi Ryh State pedagogical Institute affiliated with Kryvyi Ryh National University.
Keywords: educational e-resource; educational e-course; e-learning Moodle; foreign language